PENGARUH SOSIALISASI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJA KMELALUI PEMAHAMAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIK KEBIJAKAN AMNESTI PAJAK PADA UMKM DI KPP PRATAMA SEMARANG TENGAH DUA) - Miftahudin Hafiz; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2018)
Taxpayer compliance is the target to be achieved by the Directorate General of Taxes to increase state tax revenues. To achieve that goal, the Directorate General of Taxation issued a new policy that the Tax Amnesty. With the issuance of the tax amnesty policy aims to increase the state tax revenue, one of them through increased tax compliance. This study aimed to determine the effect of the tax dissemination and understanding of the taxpayer on tax compliance time tax amnesty policy implemented in KPP Semarang Tengah Dua. This type of research is explanatory research with 100 respondents drawn using quota sampling technique. In this study, aided by computer programs for data processing SPSS. Research results that socialization variables taxpayer and a significant positive effect on tax compliance by partial and able to explain the tax compliance of 32%. Understanding of the taxpayer is able to explain the tax compliance by 29.6%. Through research it is known that the socialization of the taxpayer and the taxpayer simultaneously understanding of positive and significant effect on taxpayer compliance in KPP Pratama Semarang Tengah Dua. Based on the research done it can be concluded that taxpayer compliance is considered to be higher .To boost compliance advised for djp to arrange the socialization for taxpayers small and medium businesses umkm especially regarding the procedures for the registration of bookkeeping well and properly, because taxpayer compliance indicators obtain that response was low enough of the respondents.